Inorganic iodine and bromine speciation in Arctic snow at picogram-per-grams levels by IC-ICP-MS - Stefano Frassati; Elena Barbaro; Claudia Rossetti; Giulio Cozzi; Clara Turetta; Federico Scoto; Marco Roman; Matteo Feltracco; Kitae Kim; Carlo Barbante; Andrea Gambaro; Andrea Spolaor (2024)
Iodine and bromine play central roles in polar atmospheric chemistry: iodine influences the atmospheric oxidative capacity and can generate cloud condensation nuclei, while bromine participates in ozone depletion reactions, known as bromine explosions. Here we present a very sensitive analytical method for Br and I speciation by coupling the ion chromatography system (IC) with an inductively coupled plasma sector field mass spectrometer (ICP-SFMS). We achieved sub-picogram per gram (pg g-1) as limits of detection (LODs) ranging from 0.4 pg g-1 for I-, 0.8 pg g-1 for IO3-, 4 pg g-1 for Br-, and 1 pg g-1 for BrO3-, respectively. These values represent a decrease of up to 30 times compared to the LODs reported in other studies. The method was validated using deep snow samples from the Svalbard Islands, collected at the end of the polar night to quantify various oxidized compounds during their seasonal minimum. In the future, this method could prove useful in the paleoclimatic study of ice cores and snow, as well as in ice chemistry research.